Ambient intelligence Second International Joint Conference on AmI 2011, Amsterdam, The Netherlands, November 16-18, 2011. Proceedings - Keyson, David V.; Maher, Mary Lou; Streitz, Norbert; Cheok, Adrian; Augusto, Juan Carlos; Wichert, Reiner; Englebienne, Gwenn; Aghajan, Hamid; Kröse, Ben J. A. (Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the Second International Joint Conference on Ambient Intelligence, AmI 2011, held in Amsterdam, The Netherlands, in November 2011. The 58 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers cover a wide range of topics such as haptic interfaces, smart sensing, smart environments, novel interaction technologies, affecting human behaviour, privacy and trust, landscape and ambient assisted living.